Length of the memory retention period depends on the extent of protein synthesis in the terrestrial slug Limax. (6th September 2016) - Suenaga, Yuko; Matsuo, Ryota
Highlights: Onset timing of amnesia shifts depending on the timing of anisomycin injection. Amnesia appears early if anisomycin is injected close in time to conditioning. Amnesia appears late if intervals are given between the injection and conditioning. The LTM phase is more graded than previously thought. Abstract: The terrestrial slug Limax can form an odor-aversion memory by the single simultaneous presentation of a food odor and an aversive stimulus. We have previously demonstrated that the long-term retention of this memory was impaired by a high-dose injection of a protein synthesis inhibitor 30 min prior to the conditioning. However, the onset of amnesia was delayed if the dose of the inhibitor was reduced or a less potent protein synthesis inhibitor was used. We thus speculated that the persistence of memory depends on the amount of newly synthesized protein following learning. In the present study, we further elaborated on this idea by injecting a high dose of anisomycin at different timings before or after conditioning, and tested the memory retention at 1, 2, 3, 7, or 14 days after the conditioning. We found that the injection of anisomycin 6 h before, or 1 h after the conditioning had no effect on memory retention for 7 days, and an injection at 30 min before and just following the conditioning impaired the memory retention at 3 days. Interestingly, the injection at 3 h before and 30 min after the conditioning did not impair the retention at 3 days but did impair retention at 7 days. Taking into account the time course of protein synthesis inhibition in the brain, our results further support the idea that the memory retention period is dependent on the amount of protein synthesized following memory acquisition.